PHYSICAL STABILITY OF HAND WASHING SOAP PREPARATIONS LIME ESSENTIAL OIL (Citrus aurantifolia) - Definingsih Yuliastuti; Dessy Ratna Sari; Nina Melinda Erzaputri (Jurnal Jamu Kusuma, 2025)
The human hand's palm is highly susceptible to the spread of bacteria and microorganisms, which can lead to infection. Pharmaceutical preparations that are able to kill germs and bacteria are soaps. Lime (Citrus aurantifolia) is a type of plant that contains essential oils that have antibacterial activity and can be used as an active ingredient in soap formulations. The purpose of this study was to determine the effect of storage cycles on the results of the physical stability test of hand soap preparations formulated with lime essential oils using the cycling test method. This test method was carried out for 6 cycles at temperatures of 4°C and 40°C for 24 hours each by testing several parameters of the physical stability of hand soap preparations, including organoleptic, homogeneity, pH, viscosity, and foam height. The results of the organoleptic stability of the soap preparation were in the form of a thick, yellow liquid and had a distinctive lime odour. The soap preparation was homogeneous during 6 cycles of storage, with an average pH of 5.98, a viscosity of 524-578 cPs, and an average foam height of 52 mm. The results of data analysis in the stability test using one-way ANOVA showed no significant difference between storage cycles, which means that the soap preparation was stable during the storage cycle.